Evaluasi Major Overhaul terhadap Efisiensi dan SFC PLTD Kotaraya - Eri Prabowoa; Trassanda Scudetto Widestomo Putra; Afristian Arief Dwiranda (JTM : JURNAL TEKNIK MESIN, 2026)
Diesel power plants remain important for isolated electricity systems because they can be operated flexibly and maintained locally. This paper evaluates the effect of major overhaul on thermal efficiency and Specific Fuel Consumption (SFC) of a 1 MW Cummins KTA50 G8 diesel engine at PLTD Kotaraya. The study used operational logsheet data, commissioning test data, before-overhaul data, and after-overhaul data. SFC was calculated from fuel mass flow and engine power, while thermal efficiency was calculated from engine power, fuel mass flow, lower heating value, and combustion efficiency. The analyzed load levels were 50%, 75%, 85%, and 100% for before and after major overhaul. The results show that SFC after overhaul was lower than before overhaul at all comparable load levels: at 50% load from 267.143 to 238.000 gr/kWh, at 75% load from 245.192 to 238.000 gr/kWh, at 85% load from 255.000 to 230.000 gr/kWh, and at 100% load from 242.857 to 229.500 gr/kWh. Thermal efficiency also increased from 33.489% to 37.590%, 36.488% to 37.590%, 35.084% to 38.898%, and 36.838% to 38.982%, respectively. The findings indicate that major overhaul improved fuel economy and thermal performance, especially when the unit operated at higher load